The analysis of Li i 6708A line through the rotational period of HD166473 taking into account Paschen-Back magnetic splitting. Issue Volume 9:Issue S302(2013) (7th August 2014) - Shavrina, A. V.; Khalack, V.; Glagolevskij, Y.; Lyashko, D.; Landstreet, J.; Leone, F.; Giarrusso, M.
Abstract: The analysis of Lii 6708 Å line was performed for 6 rotational phases distributed over the whole rotational period (~9.5 years) of HD166473. The magnetic field model was constructed based on the polarimetric measurements from Mathys et al. (2007). For each observed phase the modulus of the magnetic field was also estimated from simulation of the Feii 6147 Å, 6149 Å and Priii 6706.7 Å line profiles taking into account Zeeman magnetic splitting. The lithium abundance in each phase was obtained from fitting the observed Lii 6708 Å profile with the synthetic one calculated assuming Paschen-Back splitting and estimated magnetic field characteristics from Priii 6706.7 Å line profile.